Amino Acid Oxidation: A Combined Study of Cysteine Oxo Forms by IRMPD Spectroscopy and Simulations1. Issue 48 (3rd November 2016) - Scuderi, Debora; Bodo, Enrico; Chiavarino, Barbara; Fornarini, Simonetta; Crestoni, Maria Elisa
Abstract: The redox activity of cysteine sulfur allows numerous post‐translational protein modifications involved in the oxidative regulation of metabolism, in metal binding, and in signal transduction. A combined approach based on infrared multiple photon dissociation spectroscopy at the Centre Laser Infrarouge d'Orsay (CLIO) free electron laser facility, calculations of IR frequencies, and finite temperature ab initio molecular dynamics simulations has been employed to characterize the gas‐phase structures of deprotonated cysteine sulfenic, sulfinic, and sulfonic acids, [cysSO x ] − ( x =1, 2, 3, representing the number of S‐bound oxygen atoms), which are key intermediates in the redox‐switching chemistry of proteins. The ions show different structural motifs owing to preferential binding of the proton to either the carboxylate or sulfur‐containing group. Due to the decreasing basicity of the sulfenic, sulfinic, and sulfonic terminals, the proton bound to SO − in [cysSO] − migrates to the carboxylate in [cysSO3 ] −, whereas it turns out to be shared in [cysSO2 ] − . Evidence is gathered that a mixture of close‐lying low‐energy conformers is sampled for each cysteine oxo form in a Paul ion trap at room temperature. Abstract : Redox chameleon : Cysteine thiol oxidation can modulate protein structure, location, and functional activity. Infrared spectroscopy and computational chemistry reveal the deprotonation sites and conformational space of bare cysteine sulfenate, sulfinate, and sulfonate species (see figure).